2021
DOI: 10.3389/fimmu.2021.658896
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Overproduction and Immune System Dysregulation in alloHSCT and COVID-19 Patients

Abstract: The COVID-19 pathomechanism depends on (i) the pathogenicity of the virus, (ii) ability of the immune system to respond to the cytopathic effect of the virus infection, (iii) co-morbidities. Inflammatory cytokine production constitutes a hallmark of COVID-19 that is facilitated by inability of adaptive immunity to control virus invasion. The effect of cytokine release syndrome is deleterious, but the severity of it depends on other confounding factors: age and comorbidities. In this study, we analyze the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 145 publications
1
11
0
Order By: Relevance
“…Among the factors underlying the development of the severe and critical forms of COVID-19, advanced age [3], comorbidities [3], hyperactivation of the immune system [3,4] are proven to have a central role, hyperactivation of the immune system results in the cytokine storm, which is characterized by the synthesis and release of high levels of proinflammatory cytokines [3,4]. In this way, cytokine storm plays a major role in Covid-19 pathogenesis [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors underlying the development of the severe and critical forms of COVID-19, advanced age [3], comorbidities [3], hyperactivation of the immune system [3,4] are proven to have a central role, hyperactivation of the immune system results in the cytokine storm, which is characterized by the synthesis and release of high levels of proinflammatory cytokines [3,4]. In this way, cytokine storm plays a major role in Covid-19 pathogenesis [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 7p15.3 ( IL6 –174C allele) has been related to the severity of pneumonia and COVID‐19. IL6 also affects the CD4 + T cells' fate and causes the COVID‐19 severity 61–63 . In addition, IL6 , IL10 , and IL12B SNPs have been associated with daily death rates mainly due to hypertension, cardiovascular diseases, obesity, and asthma 64–67 .…”
Section: Interleukins Polymorphismsmentioning
confidence: 99%
“…IL6 also affects the CD4 + T cells' fate and causes the COVID‐19 severity. 61 , 62 , 63 In addition, IL6 , IL10 , and IL12B SNPs have been associated with daily death rates mainly due to hypertension, cardiovascular diseases, obesity, and asthma. 64 , 65 , 66 , 67 In a study, among severely ill COVID‐19 patients ( n = 100), the IL6 gene was significantly expressed higher compared to that in the control population ( n = 324) which was correlated to the higher mortality rate.…”
Section: Interleukins Polymorphismsmentioning
confidence: 99%
“…The humoral and cellular immunity uses T cells, B cells, natural killer (NK) cells in fighting viral infections and an effective immune response depends on the activation of cytotoxic CD8+ T cells through killing the infected cells. 3 Results reported since the onset of pandemic showed that more than half of the patients had decreased lymphocyte counts, and pathological findings showed that patients who died of this disease had higher levels of pro-inflammatory CCR6 + Th17 + CD4 + T cells. 4 This infers that the overactivation of T-cells united with the high CD8 T cells cytotoxicity is partially responsible for the observed severe immune injuries in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 95%